UiTM’s ORL: a year with COVID-19 - Mat Barhan, Noor Shairah; Sobani, Muhamad Ariff (Faculty of Medicine, 2021)
The COVID-19 pandemic took the world by surprise. The past eighteen months have been incredibly challenging. The pandemic threw systemic shortfalls – or gaps- into sharp relief across medical education and healthcare systems the world over. While many will remember COVID-19 as a source of disruption, it will also be viewed as a catalyst for transformation brewing for the past decade. With the sudden shifting away from physical classes and towards remote learning, many innovations and digital platforms have been created and improvised to disseminate knowledge virtually. ORL surgeons have had to utilize highly invasive surgical procedures to anatomical regions usually tricky to access.